CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) TO DEVELOP WRITING SKILLS IN ENGLISH - Montoya, Olga Isabel Reinoso (2022)
In a world of permanent change, traditional language teaching methods do not solve the communicative needs in foreign languages ​​that favor knowledge and adaptation to changing educational contexts. The CLIL method is widely used to develop skills both in the learning language and in other areas of knowledge, it allows for the strengthening of teaching capacities to assume the teaching of contents of the different subjects in a foreign language. The objective of this bibliographic review is to collect significant and existing information on the CLIL method and contribution of this method in the educational field. The documentary descriptive approach of recent research related to the subject of study is used, based on the theoretical foundations of bilingual education. The literature review shows that by teaching the foreign language as a vehicle to instruct content from other subjects, students understand the need to learn the language to seize the knowledge of the subject and allows teachers to explore their own teaching context, reflect and identify factors that can improve their teaching practice, especially in the inclusion of writing activities in English.